Transcriptome analysis predicts mode of action of benzimidazole molecules against Staphylococcus aureus UAMS‐1. Issue 4 (21st February 2019) - Chauhan, Deepika; Hati, Santanu; Priyadarshini, Richa; Sen, Subhabrata
Abstract: Antimicrobial drug resistance is one of the most critical problems that plagued the human race in modern times. Discovery of novel antibiotics is important to counter this threat. Accordingly, herein we have reported the discovery of substituted benzimidazole class of molecules with antimicrobial property (specifically against Staphylococcus aureus ). They were initially identified through a random screening and a novel catalytic synthetic strategy was utilized to access them. in vitro screening and phenotypic profiling revealed the antimicrobial nature. De novo transcriptome and gene analyses predicted the putative targets. This work provides a solid foundation for developing the benzimidazoles as a target specific antimicrobial preclinical candidate.